Application of Purified Filter Axis Trajectory in Gearbox Failure Identification - Lü Zuopeng; Peng Lou; Jin Feng; Kun Qin; Lulu Qian (Jixie chuandong)
According to the phenomenon of the external meshing herringbone teeth test of fan drive gearbox, based on the knowledge of dynamics analysis and failure theory, a set of method for purifying and filtering axis trajectory is established. The failure type is determined by comparing the variation trend of the purified filter axis trajectory diagram and the vibration data. The problem can be detected earlier and serious accidents can be avoided by the purified filter axis trajectory.